Production Of Cellulase And Xylanase Via Solid State Fermentation And Its Application In The Enzymatic Deinking Of Laser Printed Waste Papers. - Pang, Pei Kheng; Lee, Chee Keong; Ibrahim, Darah; Che Omar, Ibrahim (2006)
The work deals with the production of cellulase and xylanase by local isolates via solid state fermentation SSF) processes for the application in the enzymatic deinking of laser printed wastepapers.